Fostering Students’ Creative Attitudes in Laboratory Inquiry Activities: Learning about Extraction by Utilizing Dragon Fruit Skins - Sunyono, Sunyono; Meristin, Annisa (FKIP Universitas Lampung, 2024)
Abstract: Fostering Students’ Creative Attitudes in Laboratory Inquiry Activities: Learning about Extraction by Utilizing Dragon Fruit Skins. Objective: The current study aimed to determine the effect of the laboratory inquiry learning model on students’ creative attitudes. Methods: This research was conducted using a pretest-posttest non-equivalent control group design and data analysis was carried out using descriptive statistical analysis n-Gain and t-test. Data collection techniques were carried out by means of observation and questionnaires. Findings: The results showed that there was a significant influence on the development of creative attitudes, especially on indicators of mutual respect. Strategy used in this research was successful in increasing students’ activities in the classroom. Conclusion: Laboratory inquiry activities by utilizing dragon fruit skins can be used as a attractive learning strategy to improve students’ creative attitude in learning about extraction. Keywords: laboratory inquiry, creative attitude, learning about extraction.DOI: http://dx.doi.org/10.23960/jpp.v14.i1.202432